Recent Understanding on Diagnosis and Management of Central Nervous System Vasculitis in Children. (12th September 2012) - Iannetti, Ludovico; Zito, Roberta; Bruschi, Simone; Papetti, Laura; Ulgiati, Fiorenza; Nicita, Francesco; Del Balzo, Francesca; Spalice, Alberto
Abstract : Central nervous system vasculitides in children may develop as a primary condition or secondary to an underlying systemic disease. Many vasculitides affect both adults and children, while some others occur almost exclusively in childhood. Patients usually present with systemic symptoms with single or multiorgan dysfunction. The involvement of central nervous system in childhood is not frequent and it occurs more often as a feature of subtypes like childhood polyarteritis nodosa, Kawasaki disease, Henoch Schönlein purpura, and Bechet disease. Primary angiitis of the central nervous system of childhood is a reversible cause of severe neurological impairment, including acute ischemic stroke, intractable seizures, and cognitive decline. The first line therapy of CNS vasculitides is mainly based on corticosteroids and immunosuppressor drugs. Other strategies include plasmapheresis, immunoglobulins, and biologic drugs. This paper discusses on current understanding of most frequent primary and secondary central nervous system vasculitides in children including a tailored-diagnostic approach and new evidence regarding treatment.